PENALIZAR EN MATERIA AMBIENTAL LA FALTA DE CONSERVACION DEL MEDIO AMBIENTE - VALDIVIESO ELIZALDE, ANDREA DENISSE (2016)
This thesis carries out the juridical studio of legal problems related to the environment and its legal application regarding to the sanctions imposed in the Integral Penal Organic Code about the crimes occasioned against the environment. Whit this reality I look for to analyze the importance to institute a legal reform to the Integral Penal Organic Code and its article 254. Through of this reform the sanctions provided in that article will be more rigorous for whose break the law regarding to environmental offenses. And as we know the article 397 of the Constitution of the Republic of Ecuador mentions that the State will take the necessary measures in case of environmental damages, in order to guarantee the health and ecosystem restoration; It is also the Law of Forestry and Conservation of Natural Areas and Wildlife, Article 57 and following in which refers to the protection that should be in the nature by the Ministry of Environment who will control prevent fires, pests, diseases among others and likewise that entity organized educational campaigns to prevent and combat forest fires. Also in this research he has conducted surveys and interviews conducted a public select even knowledgeable of this branch, such as legal professionals, what they have expressed different opinions about the environment and how they can contribute to more secure and less vulnerable; moreover the proposed legal reform is clear as to amend an article of the Criminal Code Integral because I think these sanctions are not going according to environmental damage. In this sense, with the arrivals conclusions I pretend to call the attention of legislators and legal theorists to legislate, develop and specify their appropriate criterions so that this important reform will be applied; in the same way with the recommendations basically go to the Ministry of Environment regarding training it is, the state, to contribute to the dissemination of environmental, National Assembly regulations regarding legal reform, and Bar of the country to promote environmental law through seminars.